Unjuk Rasa Anarkis: Analisis Faktor dan Peran Kepolisian dalam Penanggulangan - Dedy Indriyanto, Dedy Indriyanto (Jurnal Keamanan Nasional, 2023)
This article aims to explain the factors that influence the occurrence of anarchist demonstrations and the role of the Indonesian National Police (Polri) in dealing with anarchist demonstrations. The author uses a normative juridical approach with the primary legal data sources used being Law No. 9 of 1998 and the National Police Chief’s Regulations relating to the handling of anarchist demonstrations. The results of the research show that peaceful demonstrations became anarchic due to the presence of provocateurs from groups outside the demonstration masses. This research also found that masses of student groups carried out more anarchist demonstrations than other social groups, such as workers or political parties. This article concludes that anarchist demonstrations are not a single factor, non-processional police can also trigger anarchist demonstrations.